EFL Students’ Vocabulary Development: Using Leveled Texts in Online Reading Instruction - Settiawan, Dodi (State Islamic University of Sultan Syarif Kasim Riau, 2017)
As technology is continually evolving; this research presents one of its impacts in changing the traditional way of teaching vocabulary. Current technological applications are available for designing and implementing reading instruction in order to effectively develop students’ vocabulary knowledge. In this research, online reading instruction was designed to solve EFL students’ vocabulary learning problems in my own practice. To design it, readtheory.org as an Learning Management System (LMS) that stores and distributes leveled texts was used as technology (media) to make their vocabulary study easy, interesting, practical, and even enjoyable. The research findings show that the designed instruction help them to read leveled texts a lot and they reap the reward of their reading that is expanding existing vocabulary knowledge and acquiring new vocabulary. Therefore, reading leveled texts a lot cannot only be designed to improve reading skills and strategies. But, it also can be designed into activities for improving or developing EFL students’ vocabulary knowledge.